2014
DOI: 10.1038/tp.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid markers including trefoil factor 3 are associated with neurodegeneration in amyloid-positive individuals

Abstract: We aimed to identify cerebrospinal fluid (CSF) biomarkers associated with neurodegeneration in individuals with and without CSF evidence of Alzheimer pathology. We investigated 287 Alzheimer's Disease Neuroimaging Initiative (ADNI) subjects (age=74.9±6.9; 22/48/30% with Alzheimer's disease/mild cognitive impairment/controls) with CSF multiplex analyte data and serial volumetric MRI. We calculated brain and hippocampal atrophy rates, ventricular expansion and Mini Mental State Examination decline. We used false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
4
30
0
1
Order By: Relevance
“…A higher VEGF level was associated with larger baseline hippocampal volume, less hippocampal atrophy over time, and less cognitive decline over time. Interestingly, the neuroprotective effect of VEGF appeared strongest in the presence of enhanced AD biomarkers, consistent with previous reports in Aβ-42 participants, 13 suggesting that angiogenic factors may be particularly important in those individuals showing early hallmarks of the AD cascade. In further support of this theoretical pathway, the baseline effect of VEGF was also strongest in participants with MCI, and when performing stratified analyses, the majority of associations were driven by effects in the MCI group.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A higher VEGF level was associated with larger baseline hippocampal volume, less hippocampal atrophy over time, and less cognitive decline over time. Interestingly, the neuroprotective effect of VEGF appeared strongest in the presence of enhanced AD biomarkers, consistent with previous reports in Aβ-42 participants, 13 suggesting that angiogenic factors may be particularly important in those individuals showing early hallmarks of the AD cascade. In further support of this theoretical pathway, the baseline effect of VEGF was also strongest in participants with MCI, and when performing stratified analyses, the majority of associations were driven by effects in the MCI group.…”
Section: Discussionsupporting
confidence: 89%
“…12 Yet the mechanisms of this effect remain elusive. Our findings add to previous literature associating VEGF with various brain aging outcomes, 13 and suggests that the observed effects may have strong implications for potential interventions. For example, VEGF plays a large role in maintaining neural perfusion homeostasis.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In an RBM study using CSF samples from the ADNI cohort, several markers were associated with neurodegeneration in Aβ amyloid-positive subjects but not in Aβ amyloid-negative subjects. Lower levels of trefoil factor 3, VEGF, and chromogranin A, and a higher level of cystatin C were significantly associated with increased rates of neurodegeneration, indicating that these candidate markers potentially provide prognostic information and insights into AD pathobiology [72]. In another analysis of the multiplex RBM study of ADNI 1 CSF samples, high CSF apolipoprotein ε (apoE) levels were shown to be associated with a slower cognitive decline and decreased brain atrophy [126].…”
Section: Candidate New Biomarkersmentioning
confidence: 99%